2021
DOI: 10.11141/ia.57.18
|View full text |Cite
|
Sign up to set email alerts
|

Social Impact Archaeology: Pontefract Castle and the Gatehouse Project

Abstract: Archaeology is said to add value to development, creating a deeper sense of place, community identity as well as improving health and wellbeing. Accentuating these wider social values has been welcomed by a profession keen to broaden its public relevance and legitimacy and protect its seat at the table in modern cultural life, but how much, if at all, do the public actually benefit from developer-led archaeology? Benefits to individuals and communities from archaeology projects are often abstract, intangible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…To functionally annotate predicted genes, both Prokka (version 1.14.6) [ 80 ] and InterProScan (version 5.54–87.0) [ 81 ] were run. The synteny plot of the biotin locus was created using gggenes [ 82 ]. All six genes that make up the biotin locus (BioA-D, BioF, BioH) were individually aligned with mafft in automatic mode (version 7.490) [ 72 ] and transformed into a concatenated nucleotide alignment.…”
Section: Methodsmentioning
confidence: 99%
“…To functionally annotate predicted genes, both Prokka (version 1.14.6) [ 80 ] and InterProScan (version 5.54–87.0) [ 81 ] were run. The synteny plot of the biotin locus was created using gggenes [ 82 ]. All six genes that make up the biotin locus (BioA-D, BioF, BioH) were individually aligned with mafft in automatic mode (version 7.490) [ 72 ] and transformed into a concatenated nucleotide alignment.…”
Section: Methodsmentioning
confidence: 99%
“…According to Ellenberger and Richardson (2018, 66), 'these range from detailed assessments of learning outcomes to explorations of the impact on well-being and socio-economic profiles to simple collations of visitor numbers and anecdotal comments collected during events and activities' with 'an overall lack of methodology, a heavy reliance on anecdote, and sometimes crude measures for success'. Other writers suggest that there is an absence of an agreed evaluation methodology for more quantitative approaches to understanding (Sayer 2018;Wilkins et al 2021). A report commissioned by the national wellbeing organisation What Works Well (Pennington et al 2018), conducted by a team from the Institute of Psychology, Health and Society, University of Liverpool, and the Centre for Health Promotion Research, Leeds Beckett University, concluded that the evidence pointed towards a positive impact on individual and community wellbeing.…”
Section: Some Preliminary Observationsmentioning
confidence: 99%